Elevated HOX gene expression in acute myeloid leukemia is associated with NPM1 mutations and poor survival - Nagy, Ádám; Budczies, Jan (Journal of advanced research, 2019)
Acute myeloid leukemia (AML) is a clonal disorder of hematopoietic progenitor cells and the most common malignant myeloid disorder in adults. Several gene mutations such as in NPM1 (nucleophosmin 1) are involved in the pathogenesis and progression of AML. The aim of this study was to identify genes whose expression is associated with driver mutations and survival outcome. Genotype data (somatic mutations) and gene expression data including RNA-seq, microarray, and qPCR data were used for the analysis. Multiple datasets were utilized as training sets (GSE6891, TCGA, and GSE1159). A new clinical sample cohort (Semmelweis set) was established for in vitro validation. Wilcoxon analysis was used to identify genes with expression alterations between the mutant and wild type samples. Cox regression analysis was performed to examine the association between gene expression and survival outcome. Data analysis was performed in the R statistical environment. Eighty-five genes were identified with significantly altered expression when comparing NPM1 mutant and wild type patient groups in the GSE6891 set. Additional training sets were used as a filter to condense the six most significant genes associated with NPM1 mutations. Then, the expression changes of these six genes were confirmed in the Semmelweis set: HOXA5 (P=3.06E−12, FC=8.3), HOXA10 (P=2.44E−09, FC=3.3), HOXB5 (P=1.86E−13, FC=37), MEIS1 (P=9.82E−10, FC=4.4), PBX3 (P=1.03E−13, FC=5.4) and ITM2A (P=0.004, FC=0.4). Cox regression analysis showed that higher expression of these genes - with the exception of ITM2A - was associated with worse overall survival. Higher expression of the HOX genes was identified in tumors harboring NPM1 gene mutations by computationally linking genotype and gene expression. In vitro validation of these genes supports their potential therapeutic application in AML.
Gesehen am 29.01.2020